2015
DOI: 10.1155/2015/494285
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acids and Biogenic Amines Evolution during theEstufagemof Fortified Wines

Abstract: The current study was focused on the impact of accelerated ageing (heating step) on the amino acid and biogenic amine profiles of fortified wines. In this sense, three Madeira wines from two commonly used grape varieties (one red and the other white) were analysed during the heating, at standard (45°C, 3 months) and overheating (70°C, 1 month) conditions, following a precolumn derivatization procedure using iodoacetic acid,o-phthaldialdehyde, and 2-mercaptoethanol, carried out in the injection loop prior to RP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 31 publications
(33 reference statements)
4
18
0
Order By: Relevance
“…Similarly, Zhang et al (2013) and Nie et al (2014) also observed higher histidine levels in inoculated samples than in control silver carp sausages. By contrast, the concentration of free histidine was decreased slightly in batches H and FH inoculated with a histamine-producing microorganism (P < 0.05), suggesting free histidine was used partially to synthesise histamine, in agreement with previous reports by Rabie et al (2014) and Pereira et al (2015). There was no significant difference between batches HL and CK at day 28 (P > 0.05), presumably because the release of L. plantarum and consumption of the histamine-producing microorganism were balanced in this batch.…”
Section: Free Histidine Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly, Zhang et al (2013) and Nie et al (2014) also observed higher histidine levels in inoculated samples than in control silver carp sausages. By contrast, the concentration of free histidine was decreased slightly in batches H and FH inoculated with a histamine-producing microorganism (P < 0.05), suggesting free histidine was used partially to synthesise histamine, in agreement with previous reports by Rabie et al (2014) and Pereira et al (2015). There was no significant difference between batches HL and CK at day 28 (P > 0.05), presumably because the release of L. plantarum and consumption of the histamine-producing microorganism were balanced in this batch.…”
Section: Free Histidine Analysissupporting
confidence: 91%
“…() and Pereira et al . (). There was no significant difference between batches HL and CK at day 28 ( P > 0.05), presumably because the release of L. plantarum and consumption of the histamine‐producing microorganism were balanced in this batch.…”
Section: Resultsmentioning
confidence: 97%
“…Some authors reported an increase in total BAs concentration over time, mainly due to a release of AAs as a consequence of yeast lyses during alcoholic fermentation and to the proliferation of LABs with carboxylase activity during spontaneous MLF or induced by inoculation with selected bacterial starters (Landete et al, ; Lonvaud‐Funel, ; Marques et al, ). Anyway, it is generally agreed that the concentration of BAs is lower at the end of the alcoholic fermentation and increases mainly at the end of MLF (Guo et al, ; Pereira, Pereira, Pérez Trujillo, Cacho, & Marques, ). As reported before, MLF did not occur, probably for the high alcohol content that inhibited bacterial activity.…”
Section: Resultsmentioning
confidence: 99%
“…Aminoacids (AAs) and biogenic amines (BAs) occur together in food matrices and beverages, like wine, taking part in several transformation processes [136]. Representing the main fraction (25-30%) of nitrogen compounds in wines, AAs are an important source of nitrogen during yeast fermentation and are involved in the formation of aroma compounds [137]. Their profile and concentration in wines can be influenced by several factors, such as grape variety, climate, growing conditions (mainly nitrogen fertilization), and winemaking techniques (e.g., ageing process) [137].…”
Section: Aminoacids and Biogenic Aminesmentioning
confidence: 99%
“…Representing the main fraction (25-30%) of nitrogen compounds in wines, AAs are an important source of nitrogen during yeast fermentation and are involved in the formation of aroma compounds [137]. Their profile and concentration in wines can be influenced by several factors, such as grape variety, climate, growing conditions (mainly nitrogen fertilization), and winemaking techniques (e.g., ageing process) [137]. In grapes, AAs like leucine, valine, isoleucine, and phenylalanine are precursors of volatile compounds, whereas other AAs including methionine, phenylalanine, tyrosine, and tryptophan can be converted into α-ketoacids and metabolized into alcohols and fatty acids in yeast cells [138].…”
Section: Aminoacids and Biogenic Aminesmentioning
confidence: 99%